ANALISIS COST OF ILLNESS PENYAKIT HIPERTENSI DI RUMAH SAKIT UMUM DAERAH PRAYA, NTB - Aris fadillah; Juwita Ramadhani; Karina Erlianti; Hasniah Hasniah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The high prevalence of hypertension and the long-term of antihypertensive treatments required are the main reasons for the need of economic analysis on the costs of hypertensive treatment. This study aims to quantify direct medical cost of hypertension. This study uses retrospective cost of illness analysis in descriptive observational design with heath care perspective. Data were collected from the hospital’s management information system, patient's prescriptions and patient's medical records. Fifty-eight patient’s data were analyzed. Direct medical cost of the patient without comorbidities in stage 1 hypertension was Rp 535,660 ± 100,681, stage 2 hypertension was Rp 381,940 ± 126,423 and hypertensive crises was Rp 456,241 ± 197,959. Direct medical cost of the patients with comorbidities in stage 1 hypertension was Rp 398,750 ± 240,542, stage 2 hypertension was Rp 486,227 ± 241,136 and hypertensive crises was Rp 425,816 ± 140,898. Direct medical costs for patients with compelling indications in stage 1 hypertension was Rp 512,810 ± 152,661, stage 2 hypertension was Rp 444,183 ± 109,162 and hypertensive crises was Rp 410,364 ± 80,388. Cost for drugs was represented as the largest component of direct medical cost (37.49%) followes by cost for ward (26.54%), medical treatment fee (15.88%), medical support fee (9.05%), doctor visit fee (8.12%) and service fee (2.91%). The hypertension's stage, comorbidities and compelling indications are not affecting the cost of therapy. The rational use of drugs will decrease the cost of hypertension treatment.